Efektivitas Media E-Learning Berbasis Learning Management System (LMS) Di Era Pandemi Covid-19 - Sam, Noer Ekafitri; Idrus, Reski (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
This study aims to determine the effectiveness of e-learning media based on learning management system (LMS) in the era of the covid-19 pandemic on student learning outcomes and activities in the Information Systems study program with competence in scientific writing methodology. The research used is a quasi-experimental (quasi-experimental) with a one group pretest posttest design, namely experimental research carried out in one group that was chosen randomly and no stability and clarity test of the group’s condition was carried out before being treated. The population in this study were students majoring in Information Systems STMIK Hasan Sulur Wonomulyo. With a sample of 15 seventh semester students. The results obtained are (a) analysis of the N-Gain score on the pretest-posttest which is in the high category, which means there is a change in students’ cognitive towards the implementation of the media; (b) analysis of student activities in the very active category. Based on the research results obtained, the application of e-learning media based on the learning management system meets the effective category. Learning Management System can be used as a media reference in learning that can improve student learning outcomes and activities